2012
DOI: 10.3986/ac.v41i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Partial pressures of CO2 in epikarstic zone deduced from hydrogeochemistry of permanent drips, the Moravian Karst, Czech Republic

Abstract: Permanent drips from straw stalactites of selected caves of the Moravian Karst were studied during one-year period. A hypothetical partial pressure of CO2 that has participated in limestone dissolution, PCO2(H)=10-1.53±0.04, was calculated from the dripwater chemistry. The value significantly exceeds the partial pressures generally measured in relevant shallow karst soils, PCO2(soil)=10-2.72±0.02. This finding may have important implications for karst/cave conservation and paleoenvironmental reconstructions.Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
1
29
0
2
Order By: Relevance
“…In both caves, pCO 2 increases in the summer months, with the highest concentration observed at the end of the growing season. Similar findings are reported in Banner et al (2007), Liñán et al (2008), Faimon et al (2012), Cowan et al (2013), Mandić et al (2013), and Lang et al (2016). The pCO 2 plateau noticed in Drac between August and early November is due to this cave's particular air circulation.…”
Section: Cave Air and Water Temperaturessupporting
confidence: 85%
“…In both caves, pCO 2 increases in the summer months, with the highest concentration observed at the end of the growing season. Similar findings are reported in Banner et al (2007), Liñán et al (2008), Faimon et al (2012), Cowan et al (2013), Mandić et al (2013), and Lang et al (2016). The pCO 2 plateau noticed in Drac between August and early November is due to this cave's particular air circulation.…”
Section: Cave Air and Water Temperaturessupporting
confidence: 85%
“…Table II). Cave air pCO 2 higher than soil values has been documented in other mid latitude caves (Renault, 1968;Faimon et al, 2012b): in a study of Aven d'Orgnac, Bourges et al (2001) demonstrated that high cave air CO 2 concentrations (values up to 45 000 ppmv) are related to poor ventilation and CO 2 fluxes from the soil and epikarst entering into the cave through a microfissure network. This interpretation can also be applied for Bus del Diaol as supported by several dripwater analyses which exhibit a mean dissolved CO 2 concentration corresponding to 7290 ± 2475 ppmv with maximum values of 11800 ppmv Borsato et al, submitted for publication).…”
Section: Resultsmentioning
confidence: 90%
“…Spatial variability in pCO 2 could also be caused by spatial variability in concentrations of CO 2 gas in the vadose zone (Gulley et al 2014). While conceptual models of dissolution in karst hydrogeology textbooks generally consider CO 2 concentrations to be highest in the soil (Ford and Williams 2007), CO 2 concentrations are often higher in the vadose zone below the soil horizon (Wood and Petraitis 1984;Wood 1985;Baldini et al 2006;Benavente et al 2010;Faimon et al 2012;Peyraube et al 2012). The origin of this CO 2 gas is a combination of microbial oxidation of DOC that has been flushed into and accumulated within the vadose zone (Wood and Petraitis 1984) as well as root respiration (Wong and Banner 2010;Breecker et al 2012).…”
Section: Discussionmentioning
confidence: 99%